2002
DOI: 10.1121/1.1504857
|View full text |Cite
|
Sign up to set email alerts
|

Detection of static and dynamic changes in interaural correlation

Abstract: This study examines the relation between a static and a dynamic measure of interaural correlation discrimination: (1) the just noticeable difference (JND) in interaural correlation and (2) the minimum detectable duration of a fixed interaural correlation change embedded within a single noise-burst of a given reference correlation. For the first task, JNDs were obtained from reference interaural correlations of + 1, -1, and from 0 interaural correlation in either the positive or negative direction. For the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 32 publications
4
64
1
Order By: Relevance
“…These estimates are similar to those derived from behavioral measurements (Culling and Summerfield, 1998;Akeroyd and Summerfield, 1999;Boehnke et al, 2002). The different integration times required for 13 and 03 transitions might conceivably be implemented by a single mech-anism with a variable integration time.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…These estimates are similar to those derived from behavioral measurements (Culling and Summerfield, 1998;Akeroyd and Summerfield, 1999;Boehnke et al, 2002). The different integration times required for 13 and 03 transitions might conceivably be implemented by a single mech-anism with a variable integration time.…”
Section: Discussionsupporting
confidence: 70%
“…03 transitions were reported as movement toward the center of the head, whereas 13 transitions were described as a single focused source that is "stretching" and moving away from the center toward the two ears. The fact that the interaural correlation change was perceived as gradual, although the physical change was abrupt, may be an indication of the existence of a sliding binaural temporal integration window (Culling and Summerfield, 1998;Akeroyd and Summerfield, 1999;Boehnke et al, 2002), over which the perceived IAC value is computed. This is further discussed below.…”
Section: Behavioral Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 11 shows ⌬ thresholds toward correlation 1, from base correlation ϭ 0. The box shows the range of reported human correlation jnds from base correlation 0 (Gabriel and Colburn, 1981;Boehnke et al, 2002); the black horizontal line shows the median of the reported thresholds. When compared with thresholds from base 1, thresholds from base 0 show a similar CF dependence, are generally higher, and exhibit smaller differences between AN and TB fibers.…”
Section: Effect Of the Analysis Parametersmentioning
confidence: 99%
“…In psychoacoustic studies, sensitivity to interaural correlation has been measured extensively and systematically by mixing independent noise sources (Pollack and Trittipoe, 1959a;Gabriel and Colburn, 1981;Koehnke et al, 1986;Bernstein and Trahiotis, 1996;Culling et al, 2001;Boehnke et al, 2002). Single-neuron sensitivity to such stimuli, in which the normalized correlation is the primary parameter varied, has received little attention.…”
Section: Introductionmentioning
confidence: 99%